Baris Sesandaran Dance as a Medium in Developing Character Education - Negara, I Gede Oka Surya; Wahyuni, Ni Komang Sri; Sustiawati, Ni Luh (Badan Riset dan Inovasi Daerah Provinsi Bali, 2023)
Purpose: Sesandaran Baris Dance was created as a medium for developing character education. Research method: The creation method involves three stages, namely exploration, improvisation and forming which are still based on the basic elements of Balinese dance such as agem, tandang, tangkis, dan tangkep. The structure of the work consists of pepeson, pengawit, pengawak, pengecet, and pekaad. Furthermore, the study is descriptive qualitative in order to explain that the Baris Sesandaran dance is able to show as a medium for developing character education. Results and discussion: Baris Sesandaran Dance, a new creation inspired by the art of Barong Landung from Banjar Kaliungu Kelod Denpasar which has been stored for 17 years. This dance has a religious theme, puts more emphasis on the expression of will, performed by 8 male dancers carrying incense props, dancing while interspersed with singing songs together and shouting at each other as an identity in the Barong Landung art. This reciprocal song is called Sesandaran. Implications: The Baris Sesandaran dance is able to show as a vehicle for developing character education and as the development of the Barong Landung art in the form of a creational dance so that it can be passed on to the next generation.abstracts in English.